Rancangan Pembelajaran Fiqih dalam Konsep Kebijakan Adiwiyata Di SMP Bhakti Pertiwi Probolinggo - Chusnul Muali; Ayu Megawati (AT-TURATS, 2019)
Every individual has an important role in maintaining and caring for the environment, environmental damage is not only an obligation of the government but all communities and educational institutions also take responsibility, so the government has issued an Adiwiyata program policy in schools. The aim of the researchers was to find out how far the achievement of the Adiwiyata level and the integration of Adiwiyata in fiqh learning at SMP Bhakti Pertiwi, researchers used a qualitative approach to interpret phenomena that occur and are carried out involving various existing research methods, namely interviews and observations. The article discusses the implementation of fiqh learning in the Adiwiyata program of the Bhakti Pertiwi Middle School based on the results of the researchers concluded that the character of students in environmental education has been very good with the integration of the Adiwiyata program in fiqh learning students can practice directly how to use water and electricity.